Antibacterial and Mosquito Repellent Potential of Eight Citrus Cultivars and Their Chemical Composition - Mehwish Nawaz; Bait Ullah; Muhammad Ghazanfar Abbas; Muhammad Binyameen; Violeta Apšegaitė; Raimondas Mozūraitis; Muhammad Azeem (Horticulturae)
Citrus fruit peels are a rich source of essential oils (EOs), which contain biologically active compounds; however, they are often discarded as waste, which causes pollution. The fresh peels of eight citrus cultivars growing in Pakistan were used to extract EOs through steam distillation. Gas chromatography-mass spectrometry (GC-MS) analysis of fresh peel EOs revealed that limonene was the most abundant compound, constituting 94.5%, 96.1%, 95.3%, 93.3%, 56.2%, 91.5%, 96.4%, and 96.7% of Citrus jambhiri, C. aurantium, C. sinensis var. Malta cv. Blood Malta, C. sinensis var. Malta cv. Shakri Malta, C. limon, C. pseudolimon, C. reticulata var. Mandarin cv. Feutrell’s Early, and C. reticulata var. Mandarin cv. Kinnow, respectively. The dried peel EO of C. reticulata var. Mandarin cv. Kinnow contained 95.2% limonene. C. limon peel EO exhibited the highest antibacterial activity among all citrus peel EOs with the minimum inhibitory concentration of 312 μg/mL against Staphylococcus aureus. The C. aurantium and C. sinensis var. Malta cv. Shakri Malta peel EOs exhibited the highest mosquito repellent activity against Ae. aegypti females, providing protection for 45 min when tested at a concentration of 166 µg/cm2. This study showed C. aurantium and Shakri Malta peel EOs could be used to formulate natural mosquito repellent.